Sonic-assisted antibacterial photodynamic therapy: a strategy for enhancing lateral canal disinfection - Yanhuang Wang; Lishan Lei; Jing Huang; Zhiyu Cai; Xiaojing Huang (BMC, 2024)
Abstract Background Bacterial infections in lateral canals pose challenges for root canal treatment. This in vitro study aims to evaluate the antibacterial efficacy of sonic-assisted methylene blue mediated antimicrobial photodynamic therapy (MB-aPDT) against Enterococcus faecalis (E. faecalis) in infected lateral canals. Methods Sixty-five premolars infected with E. faecalis in lateral canals were randomly divided into five groups (n = 13) and treated with : (1) 5.25% NaOCl (positive control); (2) Saline (negative control); (3) Sonic-assisted MB-aPDT; (4) 3% NaOCl + MB-aPDT; (5) 3% NaOCl + sonic-assisted MB-aPDT, respectively. The antibacterial efficacy was evaluated by the colony- counting method (CCM) and scanning electronic microscope (SEM). Results Both 5.25% NaOCl and the 3% NaOCl + sonic-assisted MB-aPDT exhibited the most effective while comparable antibacterial effects without significant statistical difference (P > 0.05). Furthermore, the antibacterial effect of the 3% NaOCl + MB-aPDT group was significantly higher compared to that of the sonic-assisted MB-aPDT group (P < 0.05). The SEM results demonstrated notable morphological alterations in E. faecalis across all experimental groups, except for the negative control group. Conclusion The concentration of NaOCl can be reduced to a safe level while preserving its antibacterial efficacy through the synergism with the sonic-assisted MB-aPDT in this study.